Vibration energy harvesting and internal electric potential of (Na, K)NbO3/polyimide piezoelectric composites. (26th August 2021) - Yamamoto, Ryota; Hegendörfer, Andreas; Mergheim, Julia; Kakimoto, Ken-ichi
Abstract: A composite structure of piezoelectric particles and soft polymer composite materials is a promising component of vibration energy harvesters. However, the energy harvesting behavior which originates from ceramic particles inside the polymer has not been clarified. In this study, (Na, K)NbO3 /polyimide composites sheets with NKN fraction of 0–40 vol% were fabricated and open-circuit voltage was measured. The open-circuit voltage was increased nonlinearly from 0.72 to 2.21 V with increasing of the particle fraction (10%–30%) The experimental results were confirmed using a microstructure based finite element method and electric potential and electromechanical coupling coefficients were higher value in the content of 30% NKN particles. Analysis indicates that the internal electric potential inside the matrix under strain could be an important factor for macroscopic piezoelectric constant and electrical output.